Meningkatkan kemampuan pemahaman siswa dengan menggunakan metoda penemuan terbimbing pada pembelajaran geometri kelas 8 - Sukenda Sukenda; Uba Umbara; Evan Farhan Wahyu Puadi (Program Studi Pendidikan Matematika STKIP Muhammadiyah Kuningan, 2018)
The purpose of the study was to investigate whether Guided Finding Methods could improve students' understanding of geometry in class 8. The method used is Classroom Action Research. The research was done at SMP Negeri 2 Ciwaru located at Jl. Raya Sumberjaya, Desa Citikur, Kecamatan Ciwaru, Kabupaten Kuningan. The subjects of the researchs were the students of SMP Negeri 2 Ciwaru class 8 academic year 2016/2017. They were chosen because after consulting with mathematics teachers that this had major problems regarding the comprehension ability of mathematical concepts. Data collection techniques: observation, interview and questionnaire. The research was done in 2 cycles, each cycle was done in 3 sessions. Each session includes 4 stages: planning, action, observation and reflection. The results of the research as follows: Learning with guided discovery method can improve students' understanding 73.82%. With the following details on the first cycle students who reached the KKM 17 students (62.54%) with an average score of 65.74. In cycle II the number of KKM 23 students (85.19%) the average score in cycle II was 79.26. Based on the results of the research it is advisable to use guided discovery methods in improving students' comprehension skills.